The Effect of Training, Motivation, and Job Satisfaction on Economic Growth through Employee Productivity in Indonesia - Panji Suratriadi; Sabil; Rosento; Mohammad Amas Lahat; Amas Sari Marthanti; Suparman Hi Lawu (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyse the effect of training, motivation, and job satisfaction on economic growth through employee productivity. The research method used is a quantitative approach with 120 employees as respondents. The results showed that training has a positive effect on employee productivity with a coefficient of 0.550. Motivation also has a positive influence on employee productivity with a coefficient of 0.495. In addition, job satisfaction has the greatest influence on employee productivity with a coefficient of 0.750. Employee productivity is proven to have a positive and significant effect on economic growth with a coefficient of 0.006. Mediation analysis shows that training, motivation, and job satisfaction positively affect economic growth through employee productivity with coefficients of 0.601, 0.552, and 0.784, respectively. The results of this study confirm that increasing employee training, motivation, and job satisfaction can encourage higher productivity, which in turn has a positive impact on economic growth.